Attitudes des éleveurs et sensibilité des systèmes d'élevage face aux sécheresses dans les Alpes françaises - Baptiste Nettier; Laurent Dobremez; Jean-Luc Coussy; Thomas Romagny (Revue de Géographie Alpine)
Livestock farming systems in the French Alps are particularly exposed to the predicted climate change and most of them have already experienced periods of drought since the beginning of the 2000s. Faced with this risk, livestock farmers have put in place a certain number of measures and envisage introducing others in the future. For the present study, surveys were conducted among livestock farmers to identify these measures and analyses were carried out to characterise the attitudes of livestock farmers to drought conditions and to evaluate changes in the sensitivity of their livestock farming systems. With the exception of those farms with extensive irrigated areas, all the farms are seeking solutions to deal with the risks arising from droughts. One solution is to purchase fodder to compensate for the decrease in the harvests that normally provide animal feed in the winter; the amounts purchased vary with the length of wintering required. For the grazing periods, the high mountain livestock breeders and the dairy systems of the Northern Alps rely above all on extending and over-sizing the pasture areas in relation to the needs of the herds. The livestock farms of the Southern Alps also rely on the diversity of vegetation areas and a certain flexibility in the practices used to adapt to conditions experienced during the year. A succession of dry years could result in more radical breakdowns in the livestock systems. It should also be remembered that climate change is only one of the factors influencing the types of changes taking place on farms.